Prime, weakly prime and almost prime elements in multiplication lattice modules - ASLANKARAYİĞİT UĞURLU, EMEL; TEKİR, ÜNSAL (SCIENDO, 2016)
In this paper, we study multiplication lattice modules. We establish a new multiplication over elements of a multiplication lattice module. With this multiplication, we characterize idempotent element, prime element, weakly prime element and almost prime element in multiplication lattice modules.
Keywords: Multiplication lattice module; Prime element; Weakly prime element and Almost prime element; DUAL NOTION